The wages at the construction sector in short and medium term: the Chilean case - Astudillo Jiménez, Alejandro (2021)
The sector of the construction industry is one of the most demanding in terms of finding workforce. However, the determinants of short and medium term behavior of wages in the activity are unknown to the specialized literature. In this research we analyze the evolution of the wages received by the workers through three econometric test that determine temporalities of the inluence. In this analysis, we consider variables that characterize the economic situation of the country, as well as others directly related to the construction process and it´s influence in the wages of the workers. The results show that the short and medium term behavior of wages depend on the ending of the different stages of construction process, due to payment of bonuses by achivement of goals. In the other hands, the variables that characteice the economic evolution it´s not relevant in determine the behaviour of the wages of the construction´s workers. URL: https://revistas.uta.edu.ec/erevista/index.php/bcoyu/article/view/1461